Angular‐spatial analysis of factors affecting the performance of light field reconstruction. Issue 4 (4th April 2021) - Hu, Xinjue; Zhang, Lin
Abstract: As a new VR multimedia format, Light Field (LF) has received more and more attention. LF can support users to move freely within a certain range during the experience. However, the limitation of LF acquisition technology has become the main obstacle to its large‐scale application. Since the current hardware technology cannot produce a lens small enough to meet the needs of LF capture, the intensity of the collected LF image is usually insufficient. Although there are many software LF reconstruction algorithms have been proposed to make captured result denser, they all face the problem of poor generalization in the application process. In this work, it is attempted to locate the factors that affect the performance of LF reconstruction from both the angular and spatial domains. The analysis results show that it is affected not only by the edge and texture of the LF content in the spatial domain, but also by the adjacent disparity and the reflection characteristics in the angular domain. An indicator to quantify the impact of these factors on reconstruction performance is also proposed, which will be helpful to design a new generalized adaptive LF reconstruction algorithm in the future.